Absence of Superconductivity in the Hubbard Dimer Model for κ-(BEDT-TTF)2X - Dipayan Roy; R. Torsten Clay; Sumit Mazumdar (Crystals, 2021)
In the most studied family of organic superconductors <semantics>κ</semantics>-(BEDT-TTF)<semantics>2</semantics>X, the BEDT-TTF molecules that make up the conducting planes are coupled as dimers. For some anions X, an antiferromagnetic insulator is found at low temperatures adjacent to superconductivity. With an average of one hole carrier per dimer, the BEDT-TTF band is effectively <semantics>12</semantics>-filled. Numerous theories have suggested that fluctuations of the magnetic order can drive superconducting pairing in these models, even as direct calculations of superconducting pairing in monomer <semantics>12</semantics>-filled band models find no superconductivity. Here, we present accurate zero-temperature Density Matrix Renormalization Group (DMRG) calculations of a dimerized lattice with one hole per dimer. While we do find an antiferromagnetic state in our results, we find no evidence for superconducting pairing. This further demonstrates that magnetic fluctuations in the effective <semantics>12</semantics>-filled band approach do not drive superconductivity in these and related materials.